Photo-Crosslinked Polyurethane—Containing Gel Polymer Electrolytes via Free-Radical Polymerization Method - UYUMAZ, FATMANUR (My University, 2024)
Using a novel technique, crosslinked gel polymer electrolytes (GPEs) designed for lithium-ion battery applications have been created. To form the photo crosslink via free-radical polymerization, a mixture of polyurethane acrylate (PUA), polyurethane methacrylate (PUMA), vinyl phosphonic acid (VPA), and bis[2-(methacryloyloxy)ethyl] phosphate (BMEP) was exposed to ultraviolet (UV) radiation during the fabrication process. The unique crosslinked configuration of the membrane increased its stability and made it suitable for use with liquid electrolytes. The resulting GPE has a much higher ionic conductivity (1.83 × 10−3S cm−1) than the commercially available Celgrad2500 separator. A crosslinked structure formed by the hydrophilic properties of the PUA-PUMA blend and the higher phosphate content from BMEP reduced the leakage of the electrolyte solution while at the same time providing a greater capacity for liquid retention, significantly improving the mechanical and thermal stability of the membrane. GPP2 shows electrochemical stability up to 3.78 V. The coin cell that was assembled with a LiFePO4cathode had remarkable cycling characteristics and generated a high reversible capacity of 149 mA h g−1at 0.1 C. It also managed to maintain a consistent Coulombic efficiency of almost 100%. Furthermore, 91.5% of the original discharge capacity was maintained. However, the improved ionic conductivity, superior electrochemical performance, and high safety of GPEs hold great promise for the development of flexible energy storage systems in the future. Keywords: gel polymer electrolyte; UV-crosslinking; polyurethane acrylate; polyurethane methacrylate; free-radical polymerization; lithium-ion battery
Keywords: Kimya; Diğer; Temel Bilimler; Chemistry; Other; Natural Sciences; Temel Bilimler (Sci); Doğa Bilimleri Genel; Çok Disiplinli Bilimler; Kimya Uygulamalı; Natural Sciences (Sci); Natural Sciences General; Multidisciplinary Sciences; Chemistry Applied; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Multidisciplinary; Physical Sciences; gel polymer electrolyte; UV-crosslinking; polyurethane acrylate; polyurethane methacrylate; free-radical polymerization; lithium-ion battery